Financial Evaluation of the Efficiency of Performance of Conservation Agriculture and Food Security Enhancement Projects Using the Balanced Scorecard in Iraq for the Season 2022-2023 (Journal of Accounting and Financial Studies ( JAFS ), 2024)
In this research, a financial evaluation was conducted of the efficiency of the performance of the conservation agriculture and food security projects using the balanced scorecard in Iraq for the 2022-2023 agricultural season. The research aims to evaluate the performance of the local government agencies responsible with international organizations for implementing and following up on the studied projects (conservation agriculture and food security). This was done by using the balanced scorecard. The study found a set of results, the most important of which is that the Likert scale for conservation agriculture is that the learning and growth dimension ranked first, as it obtained the highest arithmetic mean of (3.75) and a standard deviation of (1.10), came in second place after... Internal operations have an arithmetic mean of (3.74) and a standard deviation of (0.85), which is less than one, which indicates that individuals’ opinions are not dispersed. The financial dimension came in third place with an average of about (3.56) and a standard deviation of about (1.64). The environmental and social dimension came in third place. The fourth had an average of (3.50) and a standard deviation of (0.73). As for the Likert results for food security, the internal operations dimension obtained the highest arithmetic mean of (3.97) and a standard deviation of about (0.50), which indicates that individuals’ opinions are not dispersed. It was followed by the learning and growth dimension, where it had a arithmetic mean of (3.96) and a standard deviation. It reached about (0.67), followed in third place by the financial dimension with an average of about (3.37) and a standard deviation of (1.20). The environmental and social dimension came in fourth place with an average of (3.02) and a standard deviation of (0.78). The study recommended publishing information boards that include instructions for the rules and regulations for each project, as well as professional safety methods for the purpose of preserving and sustaining project resources, and the necessity of not starting new projects without completing old ones and for the same work team to avoid situations of confusion and waste of time.​